Short day lengths augment stress-induced leukocyte trafficking and stress-induced enhancement of skin immune function - Bilbo, Staci D. (The National Academy of Sciences, 2002)
Environmental conditions influence the onset and severity of infection and disease. Stressful conditions during winter may weaken immune function and further compromise survival by means of hypothermia, starvation, or shock. To test the hypothesis that animals may use photoperiod to anticipate the onset of seasonal stressors and adjust immune function, we evaluated glucocorticoids and the distribution of blood leukocytes in Siberian hamsters (Phodopus sungorus) exposed to long day lengths (i.e., summer) or short day (SD) lengths (i.e., winter) at baseline and during acute stress. We also investigated the influence of photoperiod and acute stress on a delayed-type hypersensitivity response in the skin. SDs increased glucocorticoid concentrations and the absolute number of circulating blood leukocytes, lymphocytes, T cells, and natural killer cells at baseline in hamsters. During stressful challenges, it appears beneficial for immune cells to exit the blood and move to primary immune defense areas such as the skin, in preparation for potential injury or infection. Acute (2 h) restraint stress induced trafficking of lymphocytes and monocytes out of the blood. This trafficking occurred more rapidly in SDs compared to long days. Baseline delayed-type hypersensitivity responses were enhanced during SDs; this effect was augmented by acute stress and likely reflected more rapid redistribution of leukocytes out of the blood and into the skin. These results suggest that photoperiod may provide a useful cue by which stressors in the environment may be anticipated to adjust the repertoire of available immune cells and increase survival likelihood.